Caracterização de lodo gerado em estações de tratamento de água: perspectivas de aplicação agrícola - Botero, Wander Gustavo; Santos, Ademir dos [UNESP]; Oliveira, Luciana Camargo de [UNESP]; Rocha, Julio Cesar [UNESP] (Sociedade Brasileira de Química, 2009)
The work reported here involved the characterization of sludges produced at water treatment plants in Jaboticabal-SP using FeCl3 as flocculant, and in Taquaritinga-SP and Manaus-AM using Al2(SO4)3 as flocculant. An evaluation was also made of the interaction of organic matter extracted from the sludges with different metal species. The results indicated that all the sludges produced at water treatment plants have an important agricultural potential and that their use depends on the characteristics of the raw water and the type of flocculant employed in conventional treatment. The humic substances extracted from the sludges showed different affinities for metal species, favoring eventual exchanges between potentially toxic metals and macro- and micronutrients. An alternative for the use of sludge in agriculture is to pretreat it to remove potentially toxic metals and enrich it with micro- and macronutrients that can be released to the plant.
Characterization of sludge generated in water treatment plants: prospects for agricultural application
Keywords: humic substances; WTP sludge; agricultural